Novel Oral Suspensions: A Review - Kathpalia, Harsha; Phadke, Chetan (Current Drug Delivery, 2014)
An oral pharmaceutical suspension has been one of the most favorable dosage forms for pediatric and geriatric patients or patients unable to tolerate solid dosage forms. The liquid form is preferred because of the ease of swallowing and flexibility in the administration of doses. This emerging area of suspensions as applied to the pharmaceutical field are discussed in the current article enlightening the vision of the readers towards pharmaceutical formulations including nanosuspensions, non-aqueous suspensions and modified release suspensions. The emphasis in the article focuses on the essential principles involved in the process of formation of different types of suspensions and their applications, since novel oral suspensions have potential to provide various strategy systems.
Keywords: Modified release suspensions